Study of hepatoprotective effect of bearberry leaves extract under insulin resistance in rats - Matar Mazen (Scientific Route OÜ, 2021)
The aim of our study was to evaluate the antidiabetic and hepatoprotective efficacy of dry extract from bearberry leaves enriched with arginine in dexamethasone induced IR.